PERAN DUKUNGAN SOSIAL GURU TERHADAP REGULASI DIRI SISWA DALAM BELAJAR: The Role of Teacher Social Support on Self Regulated in Student Learning - Amseke, Fredericksen Victoranto; Sae, Desli; Liu, Doni Ariani Leowandri (Yayasan Al-Amin Qalbu, 2025)
Self-regulation in learning is very important for students as the student's ability to regulate, control and motivate themselves in the learning process to achieve learning achievement. One of the factors that influences self-regulation in learning is the social support of teachers at school. The aim of this research is to analyze the influence of teacher social support on self-regulation in student learning. This research uses quantitative methods. Data collection tools in the research used the teacher's social support scale and the self-regulation scale in student learning. The respondents for this research were 45 class VIII students at SMP Negeri 3 Amfoang Selatan in South Central Timor. The data analysis technique uses simple linear regression analysis. The results of this research prove that teacher social support has a positive and significant effect on self-regulation in student learning by 60.2%. This concludes that the higher the teacher's social support, the greater the student's self-regulation in learning. The presence of positive teacher social support through motivation, guidance and attention has been proven to be able to increase students' ability to self-regulate learning by involving thoughts, feelings and behavior so that they can increase learning achievement optimally